Analysis of the Role of the Jepara RTRW Regional Regulation 2023 Towards the Sustainability of Karimunjawa National Park - Putri, Awwaliya; Nada, Dewi Qodrun (Faculty of Social and Political Sciences, UIN Sunan Ampel Surabaya, 2024)
This article will discuss in depth the role of the 2023 Jepara Regional Spatial Planning (RTRW) regulation on preserving the Karimunjawa National Park in dealing with environmental damage caused by shrimp farming activities. The emergence of pros and cons between Karimunjawa communities in responding to shrimp farming activities has triggered conflict between communities. Furthermore, this study aims to determine the role of the 2023 Jepara RTRW regional regulation in dealing with existing problems of environmental damage and the conflicts that accompany it. The research method used to analyze written problem formulations is a qualitative method with data analysis in the form of descriptive analysis. Data collection was carried out through literature studies, obtained from similar research in the form of journals, articles and online news to support research. The findings obtained in this paper are the ratification of Jepara Regency Regional Regulation No. 4 of 2023 concerning Regional Spatial Planning, this regional regulation is the source of reference for the prohibition of shrimp farming activities as contained in article 90 C point 3 and article 91 C point 3. A total of 33 shrimp farming points in the Karimunjawa National Park are gradually being stopped. This regional regulation plays an effective role in reducing environmental damage due to shrimp farming activities. The expected implication of this article is that the RTRW Regional Regulation can be better understood by the public and the shrimp farming polemic can be resolved.